Granulomatous lobular mastitis. Issue 1 (March 2016) - Zhou, Fei; Yu, Li-Xiang; Ma, Zhong-Bing; Yu, Zhi-Gang
Abstract: Granulomatous lobular mastitis is an unusual breast benign inflammatory disorder with unknown aetiology. It is generally emerged with the clinical symptoms of breast mass, abscess, inflammation and mammary duct fistula. The diagnosis is made by histopathology with a chronic non-necrotizing granulomatous inflammation in lobules of the breast tissue as the microscopic feature. Therapy of granulomatous lobular mastitis consists of surgical, medication treatment or combination of both, but now researches suggest that observational management is an acceptable treatment.